DISORDERS OF LYMPHATIC AND VENOUS OUTFLOW AFTER HARVESTING OF FEMORAL VEIN FOR RECONSTRUCTION OF AORTOILIAC SEGMENT - Lyzikov А.А. (World of Medicine and Biology, 2013)
Analysis of consequences of femoral vein harvesting for aorto-iliac reconstruction is described in the report is devoted. Results of short term and remote follow-up of 10 aortoiliac reconstructions with deep femoral vein performed in Gomel regional vascular surgery department were studied. 5 patients underwent initial surgery for terminal stage of critical limb ischemia and 5 patients were operated for late complications (false aneurisms) of previous aorto-femoral bypass.